Avaliação de uma política pública de uso e ocupação do solo: estudo da implementação de condomínio e/ou loteamentos fechados na zona rural especial no município de Guaramiranga-Ceará - Pagliuca, Daniel (2009)
The disorder in the occupation of the Brazilian territory is a fact since the colonization period. Over time, the problems just changed forms but never had a solution, always leaving behind a heritage that was hard to solve. The first cities were on the coastland and soon also started to develop towards the inside of the continent. Those cities were usually located close to natural resources that suffered with the pressure exerted over the riverbed deteriorating their natural conditions. As from the 1970’s, a large cycle of debates started about urban disorder problems and unplanned occupations. After the approval of the Federal Constitution of 1988, Brazilian cities started to develop urban public policies in a new way, with legal competency to rule on the issue and power to exert their territorial order function. The approval of Law 10.257/01, which established the City Statute, defined the processing of public urban planning policies. Although a lot has been done, evolution was small, as urban plans were created and approved, however, with many flaws, little legitimacy and participation. In this context, this thesis assesses the Public Policy of Land Use and Occupation in the Rural Zone of Guaramiranga, based on an analysis of the legitimacy of the nomenclature “Special Rural Zone” which, although not illegal, ends up generating doubts among stakeholders. The examination of the legal viability of the installation of condominiums and land plots in the rural area of the city, through a legal analysis, surveyed the problems created by conflicts between state laws that regulate the APA of Baturité, and the dictates of the Municipal Law, with legal competency to regulate land use in the rural zone. This study looks at the legal doctrine that rules the legality of condominiums and land plots, appointing that, for their regulation, here should be municipal rules to define them, and the projects should follow the rules of the federal laws that characterize them. This study intended to evaluate this public politic and propose solutions and measures needed for a better regulation of rural land use in Guaramiranga.